Introduction to thermal analysis : techniques and applications - Brown, Michael E., 1938- (Dordrecht : Springer Netherlands, 2001)
to Thermal Analysis Techniques and Applications Edited by Michael E. Brown Chemistry Department, Rhodes University, Grahamstown, South Africa KLUWER ACADEMIC PUBLISHERS NEW YORK, BOSTON, DORDRECHT, LONDON, MOSCOW eBook ISBN: 0-306-48404-8 Print ISBN: 1-4020-0472-9 ©2004 Kluwer Academic Publishers New York, Boston, Dordrecht, London, Moscow Print ©2001 Kluwer Academic Publishers Dordrecht All rights reserved No part of this eBook may be reproduced or transmitted in any form or by any means, electronic, mechanical, recording, or otherwise, without written consent from the Publisher Created in the United States of America Visit Kluwer Online at: http://kluweronline. com and Kluwer's eBookstore at: http://ebooks. kluweronline. com CONTENTS Preface to the First Edition, Chapman & Hall, London, 1988 ix About the First Edition of this Book x Preface to the Second Edition xi 1. INTRODUCTION 1. 1 Definition and History 1 1. 2 Thermal Analysis Instruments 4 References 11 2. THERMAL EVENTS 2. 1 Introduction 13 2. 2 The Solid State 13 2. 3 Reactions of Solids 14 2. 4 Decomposition of Solids 15 2. 5 Reaction with the Surrounding Atmosphere 16 2. 6 Solid-Solid Interactions 16 References 17 3. THERMOGRAVIMETRY (TG) Introduction 3. 1 19 3. 2 The Balance 19 3. 3 Heating the Sample 21 3. 4 The Atmosphere 24 3. 5 The Sample 26 3. 6 Temperature Measurement 26 3. 7 Temperature Control 28 Sample Controlled Thermal Analysis (SCTA) 29 3. 8 3. 9 Calibration 36 3. 10 Presentation of TG Data 37 3.
Thermal Events -- Thermogravimetry (TG) -- Differential Thermal Analysis (DTA) and Differential Scanning Calorimetry (DSC) -- Thermoptometry -- Thermomechanometry -- Combination of Thermal Analysis Techniques -- Evolved Gas Analysis (EGA) -- Less-Common Techniques -- Reaction Kinetics from Thermal Analysis -- Purity Determination Using DSC -- Conclusions.
Elektronická reprodukce.
Keywords: fyzikální chemie; termická analýza; polymery; thermal analysis; physical chemistry; polymers; e-knihy online; e-books online